PENGARUH KELELAHAN EMOSIONAL TERHADAP KEPUASAN KERJA DAN DAMPAKNYA TERHADAP KINERJA GURU - Sholikhan, Sholikhan (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2009)
A teacher has an important and heavy task in the case of improving the intelect of a particular society. Beside being an educator, a teacher also has a role as a trainer, an exchange agent, and a parent for a learner. Because of having such important and heavy task, s/he may lack of the emotional resourches. If a teacher faces the case continously, s/he will have emotional exhaustion, so that it may influence the working satisfactory and the teacher’s performance.This study aimed to analyze the direct effect and indirect effect of the emotional exhaustion through the teacher’s working satisfactory for the teacher’s performance. The sample of the study is the population of 137 teachers in MAN 3 Malang and MTsN 1 Malang. The research methods applied for the study are collecting data and distributing a questionaire, whilst the data analysis used is path analysis. The result of the study shows that teachers in MAN 3 Malang and MTsN 1 Malang have high tension of emotional exhaustion, while the working satisfactory and the teacher’s performance are categorized adequate. The emotional exhaustion has negative effects for the working satisfactory. It means when the emotional exhaustion among teachers in MAN 3 Malang and MTsN 1 Malang is high, the working satisfactory is low. The working satisfactory has positive effect for the teacher’s performance. As the working satisfactory is high, the teacher’s performance will be high. The emotional exhaustion has negative direct effect for the teacher’s performance. When the emotional exhaustion among teachers in MAN 3 Malang and MTsN 1 Malang is high, the teacher’s performance is low. The emotional exhaustion does not have indirect effect for the teacher’s performance through the working satisfactory.